DIPG-09. HDAC INHIBITION IN THALAMIC AND SPINAL CORD H3K27M+ DIFFUSE MIDLINE GLIOMA. Issue 2 (22nd June 2018) - Kreimer, Sara; Lin, Grant; Woo, Pamelyn; Monje-Deisseroth, Michelle
Abstract: BACKGROUND: Diffuse midline gliomas (DMG), including diffuse intrinsic pontine gliomas (DIPG), are the leading cause of brain tumor-related deaths in children. There are no effective treatments and median survival remains dismal. Genomics identified a mutation in the majority of DMGs, a lysine to methionine substitution (K27M) in histones 3.1 and 3.3, which causes changes in gene expression that promote gliomagenesis. Panobinostat, a multiple histone deacetylase (HDAC) inhibitor, was one of the most effective agents against patient-derived DIPG cell cultures and xenograft models in previous studies and is presently in clinical trial for DIPG. HDAC inhibition with panobinostat may also exhibit activity against H3K27M+ DMG of the thalamus and spinal cord. METHODS: Patient-derived thalamic and spinal cord H3K27M+ DMG cell cultures were treated with single agent panobinostat at a range of concentrations. Cell viability was evaluated using the CellTiter-Glo assay. Panobinostat was systemically administered to murine models of luciferase-expressing spinal cord H3K27M+ DMG. Response to panobinostat was evaluated with IVIS in vivo imaging. RESULTS: HDAC inhibition with panobinostat significantly decreases cell proliferation with an IC50 of 30 nM and 41 nM in the spinal cord and thalamic glioma patient-derived cell cultures respectively. Panobinostat slowed tumor growth in spinal cord glioma orthotopic xenografts compared to vehicle controls. CONCLUSION: This study suggests that HDAC inhibition with panobinostat may also be beneficial for thalamic and spinal cord H3K27M+ DMG.